Fisheries and aquaculture by-products modulate growth, body composition, and omega-3 polyunsaturated fatty acid content in black soldier fly (Hermetia illucens) larvae - Arena, Rosaria; Manuguerra, Simona; Curcuraci, Eleonora; Cusimano, Maria; Lo Monaco, Daniela; Di Bella, Calogero; Santulli, Andrea; Messina, Concetta Maria (Frontiers in Animal Science, 2023)
The black soldier fly BSF (Hermetia illucens (L.)) is one of the most promising species for the production of ingredients, mainly protein, useful for animal feed formulation, thanks to its ability to convert organic waste into high-valuable biomass. However, the low percentage of n-3 series polyunsaturated fatty acids (PUFA) in its fatty acids profile is one of the limiting factors for the utilization of BSF in artificial foods for fish. Recent studies have highlighted that wastes derived from different agro-food value chains could be able to affect the BSF larvae nutritional composition, according to the composition of the wastes used as larvae growing substrate. Due to the significant content of n-3 PUFA in marine products, both in the edible and in by-product fractions, in this study, different sources of fish by-products were included in experimental diets for BSF to evaluate the effect of its addition on the final nutritional profile of BSF pre-pupae. One control diet and five experimental diets were prepared to feed BSF larvae: wheat bran as control diet (diet B), by-catch from Mediterranean Sea trawl fishery (Diet F), Parapenaeus longirostris processing by-products (diet S), aquaculture processing by-products (diet R), Thunnus albacares processing by-products (diet T) and Engraulis encrasicolus processing by-products (diet A). In this study the effects of the different diets were analysed on growth, body composition and fatty acids profile of BSF larvae and pre-pupae. The obtained results showed that the different experimental diets affected total lipids content and fatty acids composition, respect to the control. A significant increase of EPA and DHA in BSF larvae and pre-pupae fed with all fish by-products was observed in particular in larvae and pre-pupae fed with diet A, attesting that the utilization of fish processing by-products is a suitable solution to improve the nutritional value of insects in view of their employment as ingredients in aqua feeds. The reuse of marine by-products can contribute to the "zero waste" goal increasing the sustainability of the fishery value-chain and the formulation of new valuable products.